Pengaturan Arus dan Waktu Kerja Relay Proteksi Arus Gangguan Tanah Pada Penyulang 20 KV di PT PLN (Persero) Gardu Induk Sei Rotan : Setting Current and Working Time of Ground Fault Current Protection Relay on 20 KV Feeder at PT PLN (Persero) Sei Rotan Substation - Verawati , Verawati; Saputra , Ngairan Banu (Jurnal Ilmiah Tenaga Listrik, 2022)
Abstract To avoid the spread of fault in an area where fault occurs, a protective equipment is needed. One of the protection equipment to avoid the spread of such fault is the Ground Fault Relay (GFR). The goal of this research was to determine the current and working time of the earth fault current protection relay on the 20 KV feeder. This research method is a research method by means of observation, data collection and testing and analysis for the current and working time of the earth fault current protection relay. The place for data collection is at the PLN Sei Rotan Substation, which is located at Jalan Medan Batang Kuis Km. 11, Lr. VII, Sei Rotan. testing the characteristics of the pick-up current and reset/drop off current on the 20 KV side obtained a do/pu of 96% and is in the good category for the system, while testing the working time of the GFR relay when the fault current is 0.47 A; 0.705 A and 1.175 A respectively the relay working time is 1.107s; 0.693 s and 0.470 s and these results are in accordance with the standard inverse. The working time of the ground fault relay on the incoming side of 20 kV is faster than the working time of the ground fault relay on the 150 kV primary side. This is because the interference on the incoming side does not spread to the 150 kV primary side so that the interference can be isolated as small as possible. if the test results are not in accordance with the test standards, it is advisable to replace the relay immediately to maximize system performance. Keywords: OCR, GFR, proteksi, inverse Abstrak Untuk mencegah meluasnya gangguan pada suatu area yang terjadi gangguan maka di perlukan suatu peralatan proteksi. Salah satu peralatan proteksi untuk mencegah meluasnya gangguan tersebut adalah Ground Fault Relay (GFR). Tujuan penelitian ini adalah mengetahui arus dan waktu kerja relay proteksi arus gangguan tanah pada penyulang 20 KV. Metode penelitian ini adalah metode penelitian dengan cara pengamatan, pengambilan data dan pengujian dan analisa untuk arus dan waktu kerja relay proteksi arus gangguan tanah. Tempat pengambilan data dilakukan di Gardu Induk PLN Sei Rotan yang beralamat di Jalan Medan Batang Kuis Km. 11, Lr. VII, Sei Rotan. pengujian karakteristik arus pick up dan arus reset/drop off sisi 20 KV diperoleh do/pu sebesar 96% dan termasuk kategori baik untuk sistem sedangkan pengujian waktu kerja rele GFR ketika arus gangguan 0,47 A; 0,705 A dan 1,175 A masing-masing waktu kerja rele adalah 1,107s; 0,693 s dan 0,470 s dan hasil ini sesuai dengan standar inverse. Waktu kerja rele ground fault pada sisi incoming 20 kV lebih cepat jika dibandingkan dengan waktu kerja rele ground fault pada sisi primer 150 kV. Hal ini dikarenakan agar gangguan yang ada pada sisi incoming tidak menyebar ke sisi primer 150 kV sehingga gangguan dapat terisolir sekecil mungkin. jika hasil pengujian sudah tidak sesuai dengan standar pengujian, sebaiknya segera dilakukan penggantian rele untuk memaksimalkan kinerja sistem. Kata Kunci : OCR, GFR, protection, inverse